ANALISIS KETERAMPILAN GEOMETRI SISWA DALAM MENYELESAIKAN MASALAH TRANSFORMASI DAN KESEBANGUNAN GEOMETRI RUMAH ADAT OSING - AFNENDA, ADINDA BEAUTY (Kadikma, 2020)
This research aims to determine the geometry ability of class XI students in solving transformation problems and geometric building problems of the Osingese traditional house. The subjects of this study were 6 students of class XI MIPA 4 SMAN 1 Tegaldlimo. Students are given questions of geometric transformation skills and geometric building problems tests, followed by interviews. This type of research is a qualitative descriptive study. The results obtained in the transformation of skills are students with high math scores first have all skills, students with low math scores first have all skills except applied skills, students with medium mathematics scores first only have drawing skills and applied skills, and students with moderate math scores second and second low math score students only have drawing skills. As for geometric building problem skills, almost all students have all skills. The second moderate math score students and first low math students had all skills except, applied skills.